ANALISIS KOMPONEN KIMIA MINYAK KAYU CENDANA HASIL PENYULINGAN METODE KUKUS - Abdul Hakim Lukman; Bambang Wiyono (Jurnal Penelitian Hasil Hutan, 1992)
The  purpose   of  this research  is to  identify   the  chemical  components  of  sandalwood  oil by using the Gas Chromato- graphy.   The  sandalwood   oil was obtained   by  steam  and  water distillation of  sandalwood  particles  which  are passina  and not  passing  through  a  40  mesh  screener,   each for  18  and  24 hours  distilling   times.  The  identification    of  the peak  of chemical  components   were  done   by  comparing. the  relatioe retention  time  of  the peak  of  chemical  components  to  that of  the  chemical  so.lution standard,  The peak  area of each chemical component  was calculated  .by  normalizaion  method.The  result  showed   that  the  distilling of  sandalwood  particles   not  passing  40  mesh  screener  for  18  and  24  hour distilling times  each produced   oils having as many  as 26 and 28 peaks of chemical  components  respect wely. On the other hand,   the particles  passing  40  mesh screener.   distilled  for  18 and 24  hours  exhibited as many  es 28 peaks.  Nevertheles. only  eight  chemical  components   could  be identified from  them,   they  are:  a-pinene limonene α.santalene  terpineol-4, ϐ-santalene  nerolido L   B-santaloL. and farnesol.   Teroineo 1-4.   nerolidol. B.santalol  and  farnesol camponents constituled the   sandalwood   oii:  Those  where  usually  categoried  as the  total  santalol.    The   sandalwood oil distilled  from   the  larger particles   not passing  40 mesh  screener  for  18  and  24  hour distilling  times contained  the  total santalol of  79. 81 a,nd  81. 45 percent,   respectively.  Furtheremore,     the particles  passing  40  mesh  screener  distilled for  18  and 24  hours produced  oil containing  81, 74 and 80.88  percent  of  total  santalol  for  each distilling  time.